We learn from History - Kang, Gerui (Grace) (STIE Malangkucecwara, 2024)
Abstract Most business scandals are related to earnings management/manipulations. The purpose for this study is to explore the indicators/signs, incentives of earning management and techniques may be used in earnings manipulations. Firstly, this study summarizes the indicators/evidence and incentives of earnings management and what technique can be used to engage in earnings management and explores the possible reasons for the increased number of restatements in early of 2000s along with the effects of restatement on stock prices, restatement companies and investors. Then, this study uses three earnings management cases to sdemonstrate how the indicators, incentives of earnings management and techniques used by management are observed in these cases. Finally, the implications of earnings management in accounting and auditing are discussed.